Network effects in the formation of the financial industry's regulatory preferences in the European Union. (March 2020) - Chalmers, Adam William; Young, Kevin L
Abstract: This paper examines the determinants of financial industry actors' regulatory preferences—examining why some financial industry actors prefer less stringent financial regulations while others prefer more stringent regulations. The determination of preferences, we argue, can be understood as mutually dependent. How an organization is connected to other organisations through network ties may help to explain its regulatory preferences. Our empirical point of focus is financial industry lobbying in the context of the European Union (EU). Using data from nearly nine hundred lobbying letters related to legislation on banking, insurance, and securities regulation, we map out a "socialization network" that models connections between financial industry firms, their associations, as well as a broad range of other organisations and actors that are auxiliary to this community of organizations. Using these data we find evidence that organizations' preferences are informed by their location within this socialization network. Controlling for a range of other plausible factors, we find that 1) those connected via common associational ties, 2) those closer to one another in the network and 3) those more "embedded" in this network are all less likely to diverge in terms of their preferences from one another.